Autonomy and Control of State Agencies - Verhoest, K. author. aut Link
XIII, 311 p.
Keywords: By comparing the autonomy, control and internal management of public organizations, this book show how New Public Management doctrines work out in three small European states with different politico-administrative regimes. Using survey data on 226 state agencies, hypotheses drawing on organization theory and neo-institutional schools are tested.